Beginning with the Word : Modern Literature and the Question of Belief - Lundin, Roger (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2014)
"In this addition to the critically acclaimed Cultural Exegesis series, a nationally recognized scholar and award-winning author offers a sophisticated theological engagement with the nature of language and literature. Roger Lundin conducts a sustained theological dialogue with imaginative literature and with modern literary and cultural theory, utilizing works of poetry and fiction throughout to prompt the discussion and focus his reflections. The book is marked by a commitment to bring the history of Christian thought, modern theology in particular, into dialogue with literature and modern culture. It is theologically rigorous, widely interdisciplinary in scope, lucidly written, and ecumenical in tone and approach." -- Publishers website
Beginning with the word -- The sign in our time : sound and fury, suffering and significance -- Picturing the truth -- From signs to stories : language in the grasp of God -- Modern times : literature and the patience of God -- "I will restore it all" : Christ, fiction, and the fullness of time -- Defending a great hope : the word and the thing become one -- Dwelling in possibility : visions of justice, dreams of deliverance -- A good man is hard to find : Christ and the poets
Includes bibliographical references (pages 249-251) and index
Keywords: Christianity and Literature; Literature and Morals -- Literature and Theology -- Science and Literature